Pengembangan model percontohan kader siap bela negara berbasis identitas dan integritas pada organisasi kemahasiswaan - Leni Anggraeni; Sandey Tantra Paramitha; Abdul Azis; Edah Jubaedah; Taj Cyrila Aprila Syahda Difa (Jurnal Abmas, 2023)
Based on Article 27 paragraph (3), it mandates that "Every citizen has the right and obligation to participate in efforts to defend the country". So based on this mandate, the existence of student organizations is an important part of implementing state defense, especially in the campus environment which can of course be at the forefront in building state defense, especially during the COVID-19 pandemic, state defense has a vital role in being able to become a medium for building awareness. to maintain national identity and integrity. Therefore, this PkM aims to be able to develop a pilot model of cadres ready to defend the country based on identity and integrity in student organizations. The PkM program, using the participatory action study method, with 21 students as part of student organization representation within the Indonesian University of Education, with data collection techniques using questionnaires. The results of the implementation of this service program show that cadres are ready to defend the country in the climate of UPI student organizations showing a percentage of 61.9% stating that they Strongly Agree that students must have the awareness to be active and contribute to Student Organizations on campus as cadres ready to defend the country using a culturally appropriate approach respective organizations such as accustoming members to be disciplined and honest, prioritizing collective interests besides individual interests, every activity must be based on internalizing the values of Pancasila and defending the country as well as maintaining local cultures as a form of nationalism, identity and student integrity.   Abstrak Berdasarkan Pasal 27 ayat (3) mengamanatkan bahwa “Setiap warga negara berhak dan wajib ikut serta dalam upaya pembelaan negara”. Maka berdasarkan amanat tersebut, keberadaan organisasi kemahasiswaan menjadi salah satu bagian penting dalam pelaksanaan bela negara, terkhusus di lingkungan kampus yang tentunya bisa menjadi garda terdepan dalam membangun bela negara terkhusus di masa pandemi COVID-19 bela negara sangat memiliki peran vital untuk bisa menjadi media pembangunan kesadaran untuk tetap mempertahankan identitas dan integritas bangsa. Oleh karena itu PkM ini bertujuan untuk bisa mengembangkan model percontohan kader siap bela negara berbasis identitas dan integritas pada organisasi kemahasiswaan. Program PkM dengan metode kaji tindak partisipatif ini bersama 21 mahasiswa sebagai bagian dari keterwakilan organisasi kemahasiswaan di lingkungan Universitas Pendidikan Indonesia, dengan teknik pengumpulan data menggunakan kuesioner. Hasil pelaksanaan program pengabdian ini menunjukkan bahwa kader siap bela negara pada iklim organisasi kemahasiswaan UPI menunjukkan persentase 61,9 % menyatakan Sangat Setuju jika mahasiswa harus memiliki kesadaran untuk aktif dan berkontribusi dalam organisasi kemahasiswaan di lingkungan kampus sebagai kader siap bela negara dengan menggunakan pendekatan sesuai budaya organisasinya masing-masing seperti membiasakan anggota untuk disiplin dan jujur, mendahulukan kepentingan bersama di samping kepentingan individu, setiap kegiatan harus berlandaskan pada internalisasi nilai- nilai Pancasila dan bela negara serta menjaga kebudayaan-kebudayaan lokal sebagai wujud nasionalisme identitas dan integritas mahasiswa. Kata Kunci: kader; bela negara; identitas; organisasi kemahasiswaan